Evolutionary and developmental implications of asymmetric brain folding in a large primate pedigree. (1st March 2016) - Atkinson, Elizabeth G.; Rogers, Jeffrey; Cheverud, James M.
Abstract: Bilateral symmetry is a fundamental property of the vertebrate central nervous system. Local deviations from symmetry provide various types of information about the development, evolution, and function of elements within the CNS, especially the cerebral hemispheres. Here, we quantify the pattern and extent of asymmetry in cortical folding within the cerebrum of Papio baboons and assess the evolutionary and developmental implications of the findings. Analyses of directional asymmetry show a population‐level trend in length measurements indicating that baboons are genetically predisposed to be asymmetrical, with the right side longer than the left in the anterior cerebrum while the left side is longer than the right posteriorly. We also find a corresponding bias to display a right frontal petalia (overgrowth of the anterior pole of the cerebral cortex on the right side). By quantifying fluctuating asymmetry, we assess canalization of brain features and the susceptibility of the baboon brain to developmental perturbations. We find that features are differentially canalized depending on their ontogenetic timing. We further deduce that development of the two hemispheres is to some degree independent. This independence has important implications for the evolution of cerebral hemispheres and their separate specialization. Asymmetry is a major feature of primate brains and is characteristic of both brain structure and function.